FENOMENA CLAIM PALING AHLU SUNNAH (NYUNAH) DI MASYARAKAT (Kajian Atas Hadis Iftiraq al-Umam Pada Sunan Ibnu Majah No. 3981-3983) - Raffiu, Aliyya Shauma; Raharusin, Agus Suyadi (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
Disputes in understanding and opinion are something that cannot be avoided in the body of the Muslim Ummah. In the midst of a difference in understanding or debate, sometimes some groups claim that the opinion they have chosen is the correct opinion and the most appropriate to the sunnah and besides that it is a wrong opinion and not part of the ahl-Sunnah. Extreme accusations such as heresy and bid’ah (fi al-nar), there are things that are said to be heretical or fi al-nar in the hadith are those who do not conform to the congregation. From these problems a question was born: 1). How is the actual understanding related to the iftiraq al-Umam hadith?, 2). How is the relevance of the hadith of Iftiraq al-Umam with the phenomenon of the most ahl al-Sunnah (nyunnah) claims in the contemporary era. The existence of these two problem formulations basically aims to give birth to a correct understanding of the iftiraq al-Umam hadith and its relevance to the phenomenon of the most ahl al-Sunnah claims in society. To answer the formulation of the problem and realize these goals the author uses the method of Shah Hadith bi al-Maudu’ (thematic). Perselisihan pemahaman dan pendapat merupakan hal yang tidak dapat dihindarkan di tubuh Umat Islam. Di tengah-tengah adanya sebuah perbedaan pemahaman atau perbedapat tersebut terkadang sebagian kelompok meng-claim bahwasanya pendapat yang Ia pilih adalah pendapat yang benar dan paling sesuai sunah dan selain itu merupakan pendapat yang salah dan bukan bagian dari ahl-Sunnah bahkan terkadang lahir pula tuduhan-tuduhan ekstrim seperti sesat dan bid’ah (fi al-Nar), adahal yang dikatakan sesat atau fi al-nar dalam hadis ialah mereka yang tidak sesuai jama’ah. Dari permasalahan tersembut lahirlah sebuah pertanyaan: 1). Bagaimana pemahaman sebenarnya berkaitan dengan hadits iftiraq al-Umam?, 2). Bagaimana relefansi hadits iftiraq al-Umam dengan fenomena claim paling ahl al-Sunnah (nyunah) di era kontenporer. Dengan adanya dua ruusan masalah tersebut pada dasarnya bertujuan untuk melahirkan pemahaman yang benar seputar hadits iftiraq al-Umam dan relevansinya dengan fenomena claim paling ahl al-Sunnah di masyarakat. Untuk menjawab rumusan masalah dan mewujudkan tujuan tersebut penulis menggunakan metode syah hadits bi al-Maudu’ (tematik).